The role of microRNAs in primary Sjögren’s disease: deciphering regulatory networks and assessing current therapeutic perspectives - Chengzhi, Wang; Songwei, Li; Yifan, Liu; Mengmeng, Du; Huan, Li (Frontiers in Immunology, 2025)
Primary Sjögren’s disease (SjD) is a chronic systemic autoimmune disorder whose pathogenesis remains incompletely understood. Current clinical interventions demonstrate limited efficacy, yielding suboptimal therapeutic outcomes. microRNAs (miRNAs)–critical regulators of transcriptional networks–participate in SjD pathogenesis through multifaceted mechanisms. Dysregulated miRNA expression during SjD progression directly influences disease prognosis, establishing miRNAs as promising therapeutic targets. Evidence implicates macrophage polarization, apoptosis dysregulation, Th17/Treg imbalance, T/B lymphocyte dysfunction, glandular impairment, and aberrant type I interferon responses in SjD development. Notably, miR-216a-3p, miR-31-5p, and miR-155-5p modulate key signaling pathways (NF-κB, JAK/STAT, PI3K/AKT) to optimize macrophage polarization, suppress apoptosis, restore Th17/Treg equilibrium, regulate T/B lymphocyte activity, enhance glandular function, normalize type I interferon responses,thereby exerting potent anti-SjD effects. This review synthesizes recent literature to elucidate SjD pathogenesis and miRNA-mediated therapeutic mechanisms, providing a theoretical foundation for novel SjD management strategies.